2021
DOI: 10.1002/brb3.2125
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography helps distinguish multiple sclerosis from AQP4‐IgG‐seropositive neuromyelitis optica spectrum disorder

Abstract: Introduction The aim was to characterize the optical coherence tomography (OCT) angiography measures in patients with multiple sclerosis (MS) and neuromyelitis optica spectrum disorder (NMOSD) and to evaluate their disease discrimination capacity. Methods Patients with MS (n = 83) and AQP4‐IgG‐seropositive NMOSD (n = 91) with or without a history of optic neuritis, together with healthy controls (n = 34), were imaged. The main outcome measures were peripapillary retinal nerve fiber layer (pRNFL) thickness, mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…The study selection process, which is depicted in Fig. 2 , yielded the final inclusion of 18 studies with a total of 1552 evaluated eyes in MS cases (673 MSON eyes, 741 MSNON eyes, and 138 eyes without specification for the presence of ON) in addition to 1107 evaluated control eyes [ 22 , 29 , 31 , 36 , 43 , 45 57 ]. Two studies did not report the data on the MS group as a whole, so the data on the MSON group of these studies were used in the MS vs. HC analyses [ 43 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study selection process, which is depicted in Fig. 2 , yielded the final inclusion of 18 studies with a total of 1552 evaluated eyes in MS cases (673 MSON eyes, 741 MSNON eyes, and 138 eyes without specification for the presence of ON) in addition to 1107 evaluated control eyes [ 22 , 29 , 31 , 36 , 43 , 45 57 ]. Two studies did not report the data on the MS group as a whole, so the data on the MSON group of these studies were used in the MS vs. HC analyses [ 43 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…All of the 18 studies had observational designs, five of which were conducted in the United States [ 22 , 46 , 48 , 49 , 57 ], three in Italy [ 31 , 52 , 54 ], three in Turkey [ 45 , 47 , 55 ], one in China [ 29 ], one in Korea [ 50 ], one in Poland [ 43 ], one in Germany [ 56 ], one in Portugal [ 51 ], one in Egypt [ 36 ] and one in Spain [ 53 ]. In regard to MS diagnosis criteria, eight articles used the 2010 revised McDonald Criteria [ 22 , 31 , 45 , 47 , 48 , 53 , 55 , 57 ], eight articles used the 2017 revised McDonald Criteria [ 29 , 36 , 43 , 49 51 , 54 , 56 ], a single study used the 2005 revised McDonald Criteria [ 46 ], and finally, one study did not report any specific criteria [ 52 ]. Nine studies selected their case exclusively from the RRMS subtype of patients [ 19 , 36 , 43 , 45 , 47 , 49 , 53 , 54 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…An earlier study suggested that the best OCTA discriminant between NMOSD and MS is the VD reduction pattern, that is, the inferior to nasal (I/N) and I/T ratios for ON eyes and S/T and N/T ratios for non-ON eyes [ 57 ]. The combination of OCT and OCT-A parameters can also potentially differentiate the two conditions, as patients with NMOSD have a significantly lower average thickness of the pRNFL and GC-IPL and significantly smaller whole VD and perfusion density areas than those with MS [ 58 ].…”
Section: Optical Coherence Tomography With Angiography In Multiple Sc...mentioning
confidence: 99%
“…Linear regressions were performed to assess the associations between OCTA measurements of PA and those of HC, with maternal age and gestational age included as covariates. 21…”
Section: Data Analysesmentioning
confidence: 99%